Collective Modes in the Microshear Ensemble as a Mechanism of the Failure Wave - Naimark, O.; Plekhov, O.; Proud, W.; Uvarov, S. (Проблемы прочности, 2008)
Results of theoretical and experimental study of failure wave phenomena are presented. A description ofthefailure wavephenomenon wasproposed in terms ofa self-similar solutionfor the microshear density. The mechanisms offailure wave generation andpropagation were classified as a delayedfailure with the delay time corresponding to the time ofexcitation ofself-similar blow-up collective modes in a microshear ensemble. Experimental study of the mechanism of the failure wave generation andpropagation was carried out using afused quartz rod and included the Taylor test with high-speed framing. The results obtained confirmed the "delayed” mechanism of the failure wave generation and propagation.